Novel insights into the function of CD24: a driving force in cancer - Altevogt, Peter; Hüser, Laura (International journal of cancer, 2021)
CD24 is a highly glycosylated protein with a small protein core that is linked to the plasma membrane via a glycosyl-phosphatidylinositol anchor. CD24 is primarily expressed by immune cells but is often overexpressed in human tumors. In cancer, CD24 is a regulator of cell migration, invasion and proliferation. Its expression is associated with poor prognosis and it is used as cancer stemness marker. Recently, CD24 on tumor cells was identified as a phagocytic inhibitor (“do not eat me” signal) having a suppressive role in tumor immunity via binding to Siglec-10 on macrophages. This finding is reminiscent of the demonstration that soluble CD24-Fc can dampen the immune system in autoimmune disease. In the present review, we summarize recent progress on the role of the CD24-Siglec-10 binding axis at the interface between tumor cells and the immune system, and the role of CD24 genetic polymorphisms in cancer. We describe the specific function of cytoplasmic CD24 and discuss the presence of CD24 on tumor-released extracellular vesicles. Finally, we evaluate the potential of CD24-based immunotherapy.
Gesehen am 14.04.2021
First published: 13 August 2020